ATTITUDES TOWARDS HIV AIDS AMONG MIDWIFERY STUDENTS IN YOGYAKARTA - Meilani, Niken; Setiyawati, Nanik (Proceedings of the International Conference on Applied Science and Health, 2019)
Methodology: This cross-sectional study was conducted among 130 applied science midwifery students in Yogyakarta who were selected by proportional sampling. A self-administered questionnaire was used in this study. Knowledge was measured through true and false statement questions and attitude towards HIV measured through Likert scale. The analysis of univariate, bivariate, and multivariate were analyzed by computer. Results: More than three fourth of the respondents were 21 years or older. The bivariate analysis found HIV information from lecturer, HIV information from clinical instructors, experience managing HIV patient, and level of knowledge were significantly associated with attitudes towards HIV/AIDS. After adjusted to other variables in multivariate analysis, the level of knowledge had the association with attitude. Particularly, poor knowledge students were 2.26 times more likely to have negative attitude towards HIV/AIDS compared to those had good knowledge. Conclusion: Knowledge was the most influencer factors of attitude toward HIV/AIDS. The midwifery education curricula may consider to have more specific information about HIV/AIDS in order to increase the student?s knowledge.